PENDIDIKAN KARAKTER KEPEMIMPINAN SISWA BERBASIS KEARIFAN LOKAL SUKU SASAK DI MAN INSAN CENDIKIA KAB. LOMBOK TIMUR - Hartono Junaedi (An-Nahdlah: Jurnal Pendidikan Islam, 2024)
This research is about character education of students based on the local wisdom at MAN Insan Cendikia Kab. East Lombok. Method research used, namely; A qualitative filed research method using a qualitative descriptive approach and using a narrative qualitative strategy to try to investigate and tell the experiences of the research object and retold by the researcher in narrative form. The results of this research are; Conceptually, student leadership character education based on the local wisdom is implemented et the School is a refers to the results of research on Lombok cultural traditions carried out by the students themselves; Apart from that, the concept of student leadership character education also refers to the positive cultural values taught and exemplified to students by teachers, and continues to refer to the values of nationalism and religious moderation by prioritizing the values of faith and science. Meanwhile, for the implementation of student leadership character education at the school is carried out by means of public speaking training, students' independence is reflected in how they are trained to be able to develop their own programs, working with their partners.